Stoneheart: A Romance - Aimard, Gustave, 1818-1883 (Salt Lake City, UT : Project Gutenberg, 2013)
"Stoneheart: A Romance" by Gustave Aimard is a novel written in the late 19th century. The story seems to revolve around themes of friendship, loyalty, and the complex nature of human relationships, set against a backdrop rich with cultural and historical elements of Mexico. The plot introduces Don Estevan and Don Fernando, two emerging friends bound by circumstances who share a strong camaraderie fueled by mutual trust and the promise of adventure. The opening of the book establishes the bond formed between Don Estevan and the bee-hunter Don Fernando, as they navigate their intertwined fates in a world hinting at danger and intrigue. As they confide in one another about personal histories and deep-seated fears, they make decisions to protect those they care about. The narrative hints at a looming threat, particularly concerning a figure known as the Tigercat, setting the stage for conflicts involving love, enmity, and survival in a wilderness fraught with peril. (This is an automatically generated summary.)
Release date is 2013-12-09
E-text prepared by Camille Bernard and Marc D'Hooghe (http://www.freeliterature.org) from page images generously made available by the Bodleian Libraries, University of Oxford (http://www.bodleian.ox.ac.uk/home)
Keywords: Apache Indians -- Fiction; Frontier and pioneer life -- Mexico -- Fiction